Influence of development factors of manufacturing industry on the economy of the North-Western Federal District - E. Yu. Shirokova (Вестник университета)
Due to constant tightening of the sanctions policy against Russia, the stable manufacturing industry is among fundamental factors of sustainability and active growth of the country’s economy. Since the beginning of 2022, sufficient efforts have been made to neutralise the negative consequences of foreign companies leaving the market and replace imported goods and technologies with domestic ones. An urgent issue is to assess importance of stable manufacturing industry for the economy of the country and its regions. For the industrially developed North-Western macroregion, which has been seriously affected by the disruption of relations with the European Union and the United States of America, the rapid restructuring and reorientation of commodity flows is an important task, alongside with the increase in production of high value-added goods based on the resources of the macroregion.   The purpose of the study was to identify how much factors of development of the manufacturing industry influence gross regional product (hereinafter referred to as GRP) per capita in the North-Western Federal District (hereinafter referred to as NWFD).   The constructed econometric model made it possible to assess the most serious factors, the increase of which will allow to influence the economy of the macroregion. It is proved that the average number of employees of small enterprises has the strongest positive impact on GRP per capita in the NWFD as its increase by 1 person leads to an increase in the resulting variable by 1,055.76 rubles, all other things being equal. Thus, currently, the activation of the manufacturing industry with more employees of small business will become a driver of recovery and sustainable development of the macroregion’s economy.